Islam As Political Religion : The Future of an Imperial Faith - Akhtar, Shabbir, 1960- (New York Routledge Taylor and Francis)
This comprehensive survey of contemporary Islam provides a philosophical and theological approach to the issues faced by Muslims and the question of global secularization. Engaging with critics of modern Islam, Shabbir Akhtar sets out an agenda of what his religion is and could be as a political entity. * Exploring the views and arguments of philosophical, religious and political thinkers, the author covers a raft of issues faced by Muslims in an increasingly secular society. Chapters are devoted to the Qur'an and Islamic literature; the history of Islam; Sharia law; political Islam; Islamic ethics; and political Islam's evolving relationship with the West. Recommending changes which enable Muslims to move from their imperial past to a modest role in the power structures of today's society, Akhtar offers a detailed assessment of the limitations and possibilities of Islam in the modern world.
Includes Index and Notes.
Keywords: Religion and Politics -- Islam and Culture -- Islam and Politics